Improving Speaking Skills through Fairy Tales in Indonesian Language Learning - Wahyu Kurniawati; Annisa Triardianti; Rahma Kurnia Novitasari; Arnel S. Travero (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2023)
This study aims to improve the speaking skills of third grade students of a primary school in Central Java, Indonesia using fairy tales as media. Based on the results of observations, it was found that the increase in speaking skills in the third-grade Indonesian material in a primary school in Central Java, Indonesia  was relatively low. This is indicated by the achievement of student assessment results that have not been completed or have not reached the KKM (Maximum Completeness Criteria) which is 78. The percentage of speaking skill scores of 13 students, 6 students (46%) who completed or passed the KKM while 7 students (54%) did not complete or pass the KKM. The method used in this research is Classroom Action Research (CAR). Classroom Action Research is the result of the development of action research. Action research itself was developed with the aim of finding solutions to problems in the classroom. The result of this research showed that prior to the implementation only six students (46%) completed the KKM. In the first cycle it increased to eight students (69%). Then there was an increase from cycle I to cycle II resulting to eleven students (84%) who completed the KKM. Therefore, it can be concluded that storytelling media in Indonesian language learning is able to improve the speaking skills of third grade elementary school students.